(untitled) - Riviere, J. Edmond (Boca Raton, Fla., 1991)
The major objective of this handbook is to compile-in tabular form-the pharmacokinetic parameters of antimicrobial drugs used in food animals. This unique publication represents data from the FARAD (Food Animal Residue Avoidance Databank) databank, established by the authors under the auspices of the U.S.D.A. and contains significant amounts of previously unavailable information. This updated, one-of-a-kind volume even features additional data on laboratory rodents, dogs, cats, and horses in order to facilitate broader interspecies extrapolations. This easy-to-use reference is timely as well as invaluable to animal scientists, veterinarians, pharmacologists, and toxicologists who work with antimicrobials in chickens, turkeys, dairy and beef cattle, swine, goats, and sheep.
Keywords: Anti-infective agents in veterinary medicine,Veterinary drug residues,Food of animal origin; Pharmacokinetics,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Contamination,Handbooks, manuals, etc